Self-Assembly of Atomically Thin Chiral Copper Heterostructures Templated by Black Phosphorus - Coleman, Jonathan; Sanvito, Stefano; Nicolosi, Valeria; Jones, Lewys (My University, 2019)
The fabrication of 2D systems for electronic devices is not straightforward, with top‐down low‐yield methods often employed leading to irregular nanostructures and lower quality devices. Here, a simple and reproducible method to trigger self‐assembly of arrays of high aspect‐ratio chiral copper heterostructures templated by the structural anisotropy in black phosphorus (BP) nanosheets is presented. Using quantitative atomic resolution aberration‐corrected scanning transmission electron microscopy imaging, in situ heating transmission electron microscopy and electron energy‐loss spectroscopy arrays of heterostructures forming at speeds exceeding 100 nm s−1 and displaying long‐range order over micrometers are observed. The controlled instigation of the self‐assembly of the Cu heterostructures embedded in BP is achieved using conventional electron beam lithography combined with site specific placement of Cu nanoparticles. Density functional theory calculations are used to investigate the atomic structure and suggest a metallic nature of the Cu heterostructures grown in BP. The findings of this new hybrid material with unique dimensionality, chirality, and metallic nature and its triggered self‐assembly open new and exciting opportunities for next generation, self‐assembling devices.
PUBLISHED
cited By 0
Keywords: 2D materials; Black phosphorus; Chiral; Heterostructures; Nanostructures; Self-assembly